Formulation of Criminal Sanctions Policy in the Form of Fines for Illicit Trafficking of Class I Narcotics from the Perspective of Legal Justice Values (Case Study of Decision Number 427/Pid.Sus/2023/Pn Bkn) - Yoga Baya Prayurisna; Andri Winjaya Laksana (UNISSULA Semarang, 2025)
Abstract. The research aims to determine the implementation of criminal sanctions in the form of fines for the illicit trafficking of Class I Narcotics in the Bangkinang District Court, and the implementation of criminal sanctions in the form of fines for the illicit trafficking of Class I Narcotics in the Bangkinang District Court is in accordance with the objectives of punishment as a manifestation of the value of legal justice. The method used is sociological juridical, examining the legal reality experienced in the field or based on problems regarding legal matters and existing realities, with the theory of legal effectiveness and legal justice. The results of the research and discussion are that (1) the implementation of criminal sanctions in the form of fines for the illicit trafficking of Class I Narcotics in the Bangkinang District Court has normatively been carried out in accordance with statutory regulations, but has not been effective substantially and culturally according to the theory of legal effectiveness of Lawrence M. Friedman. (2) That the implementation of criminal sanctions in the form of fines for the illicit trafficking of Class I Narcotics in the Bangkinang District Court has fulfilled the aspect of legal certainty and some of the objectives of punishment, but has not fully reflected the value of legal justice in the perspective of Pancasila justice according to Yudi Latif. The justice that is upheld is still formal and has not touched the social-humanitarian dimension as a whole.